Use and selection of the aerial parts of the carob tree Prosopis pallida (Fabaceae) by reptiles, birds and mammals in Sechura (Piura - Peru) - Cruzado Jacinto, Leticia (2019)
Prosopis pallida is one component of the carob trees of the Sechura desert in northwestern Peru. It offers multiple benefits as a resource for wildlife. Following the concept of resource selection, the objective is to determine the use and selection of the aerial parts of the P. pallida by reptiles, birds and mammals, in the carob trees next to the lagoon Ñapique (Sechura, Peru). The data were taken in six conveniently selected transects and the availability of the tree was calculated after dividing it into three components, top cup, bottom cup and trunk with branches. To these components, the shade under the cup was added as the fourth component to be directly related with the tree. The Type I Design of Manly was adapted (availability and use are estimated for all individuals of the species within the study area) and the Manly Selection Ratio was used to determine the selection of tree components by wildlife. The reptiles selected the shade under the cup. Birds and mammals selected the trunk and branches. The use and selection of the different components of the P. pallida reveal the vital importance it has for the survival of wildlife in the Sechura Desert.